Phenotyping the males of mouse and rat strains with genetically defined behavioral disturbances in a model of sexual activation - M. A. Tikhonova; T. G. Amstislavskaya (Вавиловский журнал генетики и селекции)
Sexual behavior is one of the biologically highly relevant types of behavior. Sexual arousal, or an initial stage of sexual behavior, is of particular interest since it triggers all the following events but still remains the least known element of this behavior. Sexual dysfunctions are caused by aging, stress, or side effects of psychotropic drugs; they are symptoms of a variety of neurological and psychiatric disorders. Therefore, the study of sexual behavior appears to be an important step in modeling various animal pathologies and the effects of psychotropic drugs. We have performed phenotyping of animals with hereditary predisposition to catalepsy using our previous development, a model of male sexual arousal, and examined the relationship between catalepsy and sexual arousal. The main gene for a high predisposition to catalepsy was shown to be associated with the expression of sexual motivation, but not with the hormonal component of sexual arousal (increase in plasma testosterone levels following exposure to a receptive female). ASC (Antidepressant Sensitive Catalepsy) mice, proposed as a model of depression, had a decreased manifestation of sexual motivation, while male GC (Genetic Catalepsy) strain rats had enhanced sexual motivation. Noteworthy, highly excitable GC strain animals corresponding to the manic pole of bipolar disorders prevail at the current stage of breeding. Our results are in a good agreement with clinical data that indicate reduced libido in depressed patients and hypersexuality in people with bipolar disorder.